2023
DOI: 10.1002/smtd.202300377
|View full text |Cite
|
Sign up to set email alerts
|

Advances on the Application of Wide Band‐Gap Insulating Materials in Perovskite Solar Cells

Yi Guo,
Like Huang,
Chaofeng Wang
et al.

Abstract: In recent years, the development of perovskite solar cells (PSCs) is advancing rapidly with their recorded photoelectric conversion efficiency reaching 25.8%. However, for the commercialization of PSCs, it is also necessary to solve their stability issue. In order to improve the device performance, various additives and interface modification strategies have been proposed. While, in many cases, they can guarantee a significant increase in efficiency, but not ensure improved stability. Therefore, materials that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 345 publications
(447 reference statements)
0
6
0
Order By: Relevance
“…In the absence of a HTL, as the Fermi levels of ITO and PVK were close together, the contact potential was very low, which was insufficient to provide power for the extraction and separation of carriers, resulting in severe carrier recombination at the ITO/PVK interface and a low V oc . 47–49 The WF of ITO increased from 4.31 eV to 4.71 eV after MeO-2PACz modification, thereby improving the carrier transport at the ITO/PVK interface.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of a HTL, as the Fermi levels of ITO and PVK were close together, the contact potential was very low, which was insufficient to provide power for the extraction and separation of carriers, resulting in severe carrier recombination at the ITO/PVK interface and a low V oc . 47–49 The WF of ITO increased from 4.31 eV to 4.71 eV after MeO-2PACz modification, thereby improving the carrier transport at the ITO/PVK interface.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the energy gap of identical perovskite became narrow upon postprocessing by FA + . [ 71 ] Moreover, the introduction of wide‐bandgap (E g ) materials, [ 72 ] in situ growth of 2D perovskite capping layers, [ 73–77 ] and the use of interlayers with strong electric dipole moment [ 42,69,78–83 ] at the postprocessing stage can also optimize the interfacial energy band structure and enhance V bi , thereby improving charge transport and collection in PSCs (Figure 3c).…”
Section: High‐quality Perovskite Thin Films For High‐performance Pero...mentioning
confidence: 99%
“…The study found that both hygroscopic and hydrophobic polymers could be used as interfacial modifiers to enhance the humidity stability of PSCs (Figure 3d). [ 43,72 ] The introduced hydrophobic polymers can repel water from entering the perovskite films, which typically rely on various hydrophobic functional groups, such as alkyl and fluorinated groups. When the hygroscopic polymers with hydrophilic groups (i.e., carboxyl, hydroxyl, amino groups) were employed to construct barrier layers at the upper surface of perovskite films, the water molecules invading the perovskite films can be absorbed by the hygroscopic polymer interlayer, thereby preventing perovskite erosion by humid air.…”
Section: High‐quality Perovskite Thin Films For High‐performance Pero...mentioning
confidence: 99%
“…[11] A negative vacuum level change can create potential wells, capturing carriers and leading to detrimental charge accumulation. Simultaneously, akin to the tunnel effect employed in tunnel oxide passivation contact (TOPCon) solar cells, [12,13] instead of elevating the series resistance in PSCs, [14,15] the introduction of a thin insulating layer at the perovskite/HTL interface facilitates the flow of charge carriers through potential barriers in the device structure. Among the numerous other strategies, including perovskite component engineering, [16,17] solvent engineering, [18] additive engineering, [20] and interface engineering, [21][22][23] this inserted thin insulating layer with an appropriate thickness can increase the open-circuit voltage (Voc) without significantly compromising the fill factor (FF).…”
Section: Introductionmentioning
confidence: 99%